Packed bed optofluidic microreactors with Au decorated TiO2 nanoflowers for visible light photocatalytic water purification - Yujiao Zhu; Pui Hong Yeung; Tsz Wing Lo; Yao Chai; Yat Lam Wong; Ying Chen; Huaming Yang; Weixing Yu; Anatoly V. Zayats; Fengjia Xie; Xuming Zhang (npj Clean Water)
Abstract Photocatalytic water purification is an environmentally sustainable approach, but limited by low efficiency due to challenges with photocatalysts and mass transfer. Optofluidic microreactors can address these constraints, yet optimizing reactor configurations and photocatalyst designs remains challenging. Here, we present a novel planar packed-bed optofluidic microreactor (PPOM) using titanium dioxide nanoflowers (TNFs) decorated with gold nanoparticles (Au/TNFs) and conduct a pilot study on efficient visible light-driven water purification. Compared to TNFs in slurry-mode, the Au/TNFs achieve 46-fold enhancement in photodegradation efficiency due to the plasmonic effect, further boosted to 2,700-fold enhancement in the PPOM configuration by improving surface area, light harvesting, and mass transfer. The PPOM also shows a 7-fold efficiency increase compared to planar film-mode microreactors. Theoretical analysis elucidates the influences of plasmonic effect and reactor configuration on the enhanced photocatalytic activity, emphasizing the potential of integrated optofluidic systems and plasmonic-semiconductor heterostructures for sustainable water treatment and energy applications.